CHARACTERIZATION OF CARBON NANOCRISTRAL STRUCTURE BASED ON CORN COB CHARCOAL - Pelangi Eka Yuwita; Roihatur Rohmah (Department of Physics, Maulana Malik Ibrahim State Islamic University of Malang, 2022)
Carbon has an amorphous structure and a crystalline structure. The amorphous structure of carbon is usually found in charcoal, while the crystalline structure of carbon can be obtained from heat treatment. In the present study, the synthesis of carbon nanocrystals based on corn cob charcoal was successfully carried out. The synthesis began with the carbonization process of corn cobs to produce charcoal. Corn cob charcoal powder was then put into 80 mL of HCl solution and stirred using a magnetic stirrer by a speed of 750 rpm at room temperature and 80 mL of NH4OH solution was titrated into it. After the synthesis, the carbon powder was calcined at 400°C and activated using PEG 2000 template. The samples were tested using XRD (X-ray Diffraction) and SEM-EDX (Scanning Electron Microscope-Energy Dispersive X-ray). The carbon component (C) from the EDX test after the synthesis and carbonization process had an atomic percentage of 56.89% and increased by 81.06 % after PEG 2000 activation. The results of the X-ray diffraction pattern show that in all samples a broad and weak diffraction pattern was the characteristic of amorphous carbon. However, on carbon heated for 5 hours at 400°C and the addition of PEG 2000 activator, the crystal structure pattern with higher diffraction peaks was obtained and the peaks of diffraction were matched with CIF data 9008569 from phase C Graphite which had a space group P of 63 mc. SEM data on the morphology of the material showed that after receiving PEG activator, the carbon particles were split into smaller ones so that it increased in surface area and showed fairly even distribution of pores which was also seen in the surface morphology of the carbon